To solve this system of equations, we can use the method of substitution or elimination. Let's use substitution in this case.
From the second equation:
x - 5y = -20
x = 5y - 20
Now substitute x = 5y - 20 into the first equation:
-4(5y - 20) + 6y = 38
-20y + 80 + 6y = 38
-14y + 80 = 38
-14y = -42
y = 3
Now that we have the value of y, substitute it back into x = 5y - 20:
x = 5(3) - 20
x = 15 - 20
x = -5
Therefore, the solution to the system of equations is (-5, 3), which corresponds to option B.
Solve the system of equations.
−4x+6y=38
x−5y=−20
A. (5, 3)
B. (−5, 3)
C. (35, −3)
D. (−35, −3)
1 answer